Effect of Seed Size on Quality and Field Performance in Frenchbean (Phaseolus vulgaris L.) - H.S. YOGEESHA; K. BHANUPRAKASH; L.B. ΝΑΙΚ (Seed Research, 2026)
Both laboratory and field trials were conducted for two seasons to find out the effect of seed size on seed quality and field performance in frenchbean cv. Arka Komal. The study revealed that sieve size of grading screen used in Air screen cleaner could be reduced from 4.75mm to 4.35mm without any significant reduction in seed quality as well as the performance of those seeds in field in terms of pod and seed yield. By reducing the screen size, the level of rejection during processing could be brought down from 34 to 12% in some seed lots.